Does this count for marks? : a mixed methods analysis of teacher opinion of counting a large-scale assessment toward class grades - King, Sherry (My University, 2012)
The objective of this research was to gain insights on teacher opinions related to the practice of counting a portion of a large-scale educational assessment (LSA) for students' grades. [The author] anaylized the responses of 1,203 Grade 9 teachers who responded to a question on a Teacher Questionnaire administered as part of a grade 9 LSA of mathematics. Teacher opinions were clustered according to two dimensions (1) whether the teacher opined that counting the LSA for student marks motivated the studens to take the assessment more seriously, and (2) whether the teacher comment related to characteristics of the student, student behaviours, characteristics of the text, or the value students placed on the LSA. The results were that most of the teachers (85%) opined that counting the LSA for student marks motivated students to take the test more seriuosly because it raised the value of the LSA for the students, and that translated into improved test preparation and/or effort on the test. When teachers opined that counting the LSA did not motivate students, or when the teachers were undecided, teacher comments tended to focus on characteristics of the students such as program (academic or applied), ability, and anxiety.
Keywords: Grading & marking (students); Educational evaluation